Analisis Bibliometrik: Pemanfaatan Aplikasi Kahoot! Sebagai Media Evaluasi Untuk Meningkatkan Motivasi Belajar Peserta Didik - Syafina, Azwa Mirza; Mansur, Hamsi; Qomario, Qomario (Akademika : Jurnal Teknologi Pendidikan, 2025)
In the ever-evolving digital era, the integration of technology in education continues to foster the development of more interactive and effective evaluation methods. One widely adopted innovation is the Kahoot! application, used as an evaluation tool in the learning process. This study focuses on the use of Kahoot! and its impact on students' learning motivation. The objective of this research is to analyze to what extent Kahoot! can enhance learning motivation and to identify usage trends over the past five years (2020–2025). By applying bibliometric analysis and using a quantitative descriptive approach along with the VOSviewer software, this study examines the relevance and effectiveness of Kahoot! as an evaluation tool. The results show that Kahoot! significantly contributes to increasing learning motivation through interactive, fun, and innovative evaluation methods. Furthermore, the application’s use has seen rapid growth over the past five years, reflecting the growing interest among researchers in Kahoot!'s role in supporting more engaging and effective learning processes.